Ethics of Genetic Counseling in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The ethical issues raised by families involved with epilepsy are reviewed from the Faculty of Medicine and Research Centre for Public Law, Universite de Montreal, Canada; and the Foundation for Genetic Medicine, Reston, MD.